Development of Reading Literacy in Primary School Students as a Priority Objective: Pengembangan Literasi Membaca pada Siswa Sekolah Dasar sebagai Tujuan Prioritas - Mavlonbek Arabovich Doniyarov (Universitas Muhammadiyah Sidoarjo, 2022)
This scientific article explores the multifaceted development of literacy skills, focusing on reading and written speech, among primary school students in Uzbekistan. The study aims to strengthen and deepen students' knowledge and understanding of written texts, while meeting the demands of literacy requirements within the context of Uzbek capabilities. Through a systematic approach, the research employed various methods to assess the effectiveness of literacy interventions. The results revealed significant improvements in students' reading comprehension, written expression, and overall knowledge acquisition. Furthermore, the implications of this study highlight the importance of implementing comprehensive literacy strategies to optimize students' learning outcomes and promote their successful engagement in written communication. This research provides valuable insights for educational policymakers, curriculum designers, and educators seeking to enhance literacy education in similar contexts. Highlights: Comprehensive approach: This study adopts a comprehensive approach to literacy development, encompassing both reading and written speech skills among primary school students. Knowledge acquisition: The research focuses on strengthening and deepening students' knowledge and absorption of written texts, emphasizing the importance of increasing their knowledge and understanding of written materials. Implications for Uzbek capabilities: The study explores the alignment of literacy demands with Uzbek capabilities, highlighting the significance of rational and contextually appropriate approaches to literacy education. Keywords: literacy development, primary school students, reading, written speech, Uzbekistan.